Optic Disc Drusen in Children: The Copenhagen Child Cohort 2000 Eye Study. Issue 2 (June 2018) - Malmqvist, Lasse; Li, Xiao Qiang; Eckmann, Christina L.; Skovgaard, Anne M.; Olsen, Else M.; Larsen, Michael; Munch, Inger C.; Hamann, Steffen
Abstract : Background: Optic disc drusen (ODD) are seen in up to 2.4% of the general population, but the etiology and pathophysiology of the condition is still unknown. The purpose of this study was to determine the prevalence of ODD in a population-based child cohort and to determine if scleral canal diameter and fetal birth and pubertal parameters are associated with the presence of ODD. Methods: This observational, longitudinal population-based birth cohort study, with a nested case–control, included 1, 406 children. Eye examinations were performed when the children were between 11 and 12 years of age. Assessment was performed of optical coherence tomography (OCT) scans from 1, 304 children with gradable enhanced depth imaging scans of the optic disc. Results: ODD in one or both eyes were found in 13 (1.0%) of all children. All but one of the cases were found in children with scleral canal diameter in the lowest quartile (1, 182–1, 399 μm) in the nested case–control study. Children with ODD had a mean disc diameter of 1, 339 μm (interquartile range, 30 μm), whereas it was 1, 508 μm (interquartile range, 196 μm) in the 130 controls without ODD ( P < 0.001). No differences in sex, birth weight, refractive error, and Tanner stages (of puberty) were found between children with and without ODD. Conclusions: The prevalence of ODD was 1% in a large child cohort examined by OCT. ODD was found only in eyes with a narrow scleral canal, which is consistent with the hypothesis that ODD might arise as a consequence of retinal nerve fiber congestion in the scleral canal.